Adviser in educational measurement and testing: Grenada - (Mission). Project findings and recommendations - Cluff, R. B.
This is the mission report on the development of educational testing for measuring academic achievement at the primary education level to facilitate student selection for secondary education in Grenada. It deals with such examinations as intelligence tests, entrance examinations, and aptitude tests as part of admission criteria. The Common Entrance Examination (CEE) is described in detail
Keywords: Educational testing